THE IMPACT OF PRODUCTIVE DISCIPLINE STRATEGIES ON IRANIAN EFL LEARNERS’ SECOND LANGUAGE ANXIETY AND THEIR LANGUAGE ACHIEVEMENT - Parisa Abedi; Fariba Rahimi Esfahani (XXXXXXXX, 2025)
The present study was dedicated to investigating whether productive discipline strategies are effective strategies in order to reduce second language anxiety of Iranian students and improve their language achievements. To achieve the study's aim, a sample test of KET was administered to 45 students as a homogenizing test. Based on the results, the participants whose scores fell between 1 SD above and below the mean were chosen as the participants of the study and were then randomly assigned to one control and one experimental group. Those who were in the experimental group received productive strategies. The students in the control group were controlled by the traditional discipline strategy method. At the outset of the study, a pre-test was given to the participants to ensure that there were no significant difference between the experimental and control groups regarding the variable under investigation.  This study was carried out during a 40-hour course spread over 2 months. In addition, the participants were asked to fill a Second Language Anxiety Questionnaire (Howritzs, 1986) and also a 24-item questionnaire of classroom discipline (Lewis, 2001). At the end of term, all the participants were tested regarding their achievement in second language and reduction in their second language anxiety by a posttest similar to the pre-test. All in all, it was concluded that the employment of the productive strategies contribute to the improvement of students’ second language achievement and reduction of their second language anxiety.